Radiation Analysis for Two Trajectory Points of the Fire II Entry - Romain Savajano; Daniel F. Potter; Ojas Joshi; Pénélope Leyland (International Journal of Aerospace Engineering)
Numerical rebuilding of two trajectory points (t=1634 s and t=1643 s) of the Fire II mission has been carried out to predict the radiative heat flux for nonequilibrium and close-to-equilibrium conditions. The simulations have been performed with eilmer3 in an uncoupled way and using a tangent slab method for the radiation transport. Different population models (QSS and Boltzmann) have been compared, and the influence of catalytic wall condition was taken into account. An analysis on the spectral range and on the spectral resolution has also been carried out.